2009
DOI: 10.1084/jem.20081463
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells and IL-17 receptor signaling are essential for mucosal host defense against oral candidiasis

Abstract: The commensal fungus Candida albicans causes oropharyngeal candidiasis (OPC; thrush) in settings of immunodeficiency. Although disseminated, vaginal, and oral candidiasis are all caused by C. albicans species, host defense against C. albicans varies by anatomical location. T helper 1 (Th1) cells have long been implicated in defense against candidiasis, whereas the role of Th17 cells remains controversial. IL-17 mediates inflammatory pathology in a gastric model of mucosal candidiasis, but is host protective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
1,023
2
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 878 publications
(1,085 citation statements)
references
References 73 publications
(114 reference statements)
51
1,023
2
9
Order By: Relevance
“…In line with what is observed in humans 7 , Candida overgrowth occurs under conditions of defective interleukin (IL)-17F 8 or IL-17RA signalling [8][9][10] , which suggests the importance of IL-17RA signalling in preventing infection. Under specific circumstances, IL-17A may, in fact, contribute to disease susceptibility in a host-autonomous fashion, perhaps by modifying the intrinsic virulence of the fungus 8 .…”
supporting
confidence: 62%
“…In line with what is observed in humans 7 , Candida overgrowth occurs under conditions of defective interleukin (IL)-17F 8 or IL-17RA signalling [8][9][10] , which suggests the importance of IL-17RA signalling in preventing infection. Under specific circumstances, IL-17A may, in fact, contribute to disease susceptibility in a host-autonomous fashion, perhaps by modifying the intrinsic virulence of the fungus 8 .…”
supporting
confidence: 62%
“…Furthermore, we demonstrated that the fast homeostatic proliferation of CD4 + T N cells in MLNs critically contributes to the generation of gut-homing T EMphenotype Th17 cells, indicating an important role of the fast gutspecific proliferation. CD4 + T EM cells, including Th17 cells, represent a significant portion of the intestinal T cell population (27), and control bacterial infections in the gut (28,29). Therefore, the present results may further our understanding of gut-homing T EM cell differentiation in vivo.…”
Section: Discussionmentioning
confidence: 86%
“…Th17 cells produce the cytokine IL-17A, which is critically involved not only in protecting mucosal tissues from pathogenic infection (28,29) but also in pathogenesis for immune disorders, such as inflammatory bowel diseases (IBDs) and graft-versus-host disease (GVHD) (30). To understand Th17-mediated immune responses and its disorders, it is important to understand where and how these Th17 cells are generated.…”
mentioning
confidence: 99%
“…161 IL-23 promotes terminal differentiation and expansion of the Th17 cells, 162 and accumulating evidence indicates that Th17 cells are key cells in the response to C. albicans infection. 45,163,164 Th17 cells secrete numerous cytokines including IL-17A, IL-17F and IL-22, and play vital roles for immune protection against C. albicans at the majority of mucosal sites in the body. 165,166 The importance of Th17 cells in anti-Candida responses is not only portrayed by data from mice models, but also from human patients.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%